(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Karnataka occupies the third position in the natural rubber production in the country. Karnataka is considered to be a non-traditional region for growing rubber, but it is being successfully grown in the state. This study presented Goal Programming approach for maximize rubber production and planted areas of rubber and statistical planning for the cultivation of rubber plants using Goal Programming approach.